Performance analysis of cobalt metal with fluoropolymer matrix as a substrate for patch antenna. Issue 176 (21st November 2016) - Arunachalaperumal, C.; Chandru, B.
ABSTRACT: Since many decades material plays major role in all fields. In recent years, materials are more useful in specific field of science and engineering. This paper deals with micro-strip patch antenna designed using FR-4 and magneto dielectric substrate. To compare these results, CSTMWS Suite (Computer Simulation Technology Micro-Wave Studio) software is used. The results show that different substrate produce different gain and directivity based on their properties. Here, two different materials namely FR-4, Cobalt metal with fluoropolymer matrix are used as a substrate for same structure.